Consumer Groups in Public Distribution System (PDS) and Rural Development - Shunmughan, R.; Sengottuvel, E. P. (International Journal of Bio-resource and Stress Management, 2010)
The paper examines the need for consumer groups in Public Distribution System (PDS) where the major stakeholders are rural people. India is the second most populous country in the world where most of the people reside in rural areas. Majority of India’s rural population are malnourished, poor and illiterate. Poverty is an important obstacle in attaining rural development. PDS has been developed as a key mechanism of the Indian Government’s economic policy for guaranteeing the openness of food grains to the public at reasonable prices as well as for enhancing the food security for the poor. However, due to the malpractice and lack of transparency in the procedure, the PDS is still a failure in India. It is recommended that the prohibition of fraudulent activities within the PDS may happen with the active participation of rural people through the establishment of consumer groups.